Powder material parameters establishment through warm forming route - Rahman M.M.; Ariffin A.K.; Nor S.S.M.; Rahman H.Y. (2023)
This paper presents the establishment of the properties of powder materials through experimentation at elevated temperature ranging from room temperature (30 C) to 150 C. Uniaxial die compaction experiments were conducted to establish the powder properties such as densification, Young's modulus, spring-back, plastic index, elastic index, and plastic hardening coefficient. Shearing experiments were conducted to establish the temperature dependent friction coefficient. Iron powder ASC 100.29, manufactured by Hgans AB Company was used during the experiment. The results showed that the deformation properties of powder materials especially iron powder are temperature dependent. The values of some properties are increased as the compaction temperature increased and vice versa. 2010 Elsevier Ltd.